EFFECTS OF A MIXED VECTOR–SCALAR SCREENED COULOMB POTENTIAL FOR SPINLESS PARTICLES - DE CASTRO, ANTONIO S. (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2006)
The problem of a spinless particle subject to a general mixing of vector and scalar screened Coulomb potentials in a two-dimensional world is analyzed and its bounded solutions are found. Some unusual results, including the existence of a bona fide solitary zero-eigenmode solution, are revealed for the Klein–Gordon equation. The cases of pure vector and scalar potentials, already analyzed in previous works, are obtained as particular cases.